2022
DOI: 10.22541/au.166200312.22598564/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors shaping the gut microbiome of five species of lizards from different habitats

Abstract: Host-gut microbiota interactions are complex and can have a profound impact on the ecology and evolution of both counterparts. Several host traits such as systematics, diet and social behavior, and external factors such as prey availability and local environment are known to influence the composition and diversity of the gut microbiota. In this study, we investigate the influence of systematics, sex, host size, and locality/habitat on gut microbiota diversity in five lizard species from two different sites in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…In contrast, Vasconcelos et al. (2023) revealed that among five lizard species, the larger species showed a positive correlation between SVL and bacterial diversity, but this effect faded when the smallest individuals were removed. Similarly, SVL influenced the microbiota composition of Sceloporus virgatus (Bunker et al., 2022), but such effect may be driven by ontogenetic shifts since young and adult individuals were sampled in the cited study.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, Vasconcelos et al. (2023) revealed that among five lizard species, the larger species showed a positive correlation between SVL and bacterial diversity, but this effect faded when the smallest individuals were removed. Similarly, SVL influenced the microbiota composition of Sceloporus virgatus (Bunker et al., 2022), but such effect may be driven by ontogenetic shifts since young and adult individuals were sampled in the cited study.…”
Section: Discussionmentioning
confidence: 88%
“…Quasi‐Poisson error distribution and a log link function were applied to account for overdispersion in bacterial diversity using the glm function in stats v.4.3.2 (Crawley, 2007). The models included the covariates SVL (mm) and elevation (m) of the sampling site of each individual, since larger lizards tend to harbour higher gut bacterial diversity (Vasconcelos et al., 2023) and bacterial richness varies with altitude (Hernández et al., 2022; Montoya‐Ciriaco et al., 2020). Sequencing depth (number of reads per sample) was also included as a covariate as it may affect diversity estimates (Alberdi et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation